Visual Screening and Refractive Errors among School Aged Children - Ambreen Gull (Journal of Rawalpindi Medical College, 2014)
Background: To evaluate visual disability (visual function), and prevalence and pattern of refractive errors in school-aged children (5 to 16 years old). Methods: A total of 45,122 children were screened. Visual acuity measurement, ocular motility evaluation, cycloplegic autorefraction, examination of the anterior segment and fundus were performed. Results: Among 45,122 subjects, majority (65.5%) were females. Average age was 10.5 ± 3.4 years. Prevalence of uncorrected and best corrected visual acuity 6/12 or worse in at least one eye was 3.55% and 0.26% respectively. Prevalence of refractive error in this study population was 3.3%. When all of children with V/A 6/12 or less were evaluated, 1.89% had myopia and 0.63% had hyperopia. Astigmatism 0.50 D or greater was present in 0.76%. Myopia was associated with older age and female gender. Higher risk of myopia in children of older age was statistically significant. Hyperopia was inversely proportional with older age. Spectacles were needed in 3.08% children with refractive errors. Conclusions: Prevalence of reduced vision is low in school-age children. Mostly were correctable refractive error,but uncorrected refractive error, especially myopia, was common in these children.